Investigation into applicability of EQCM methods at elevated temperature for ionic liquids. (10th March 2016) - Sasaya, Naoko; Matsumiya, Masahiko; Murakami, Sena; Nishihata, Keiichi; Tsunashima, Katsuhiko
Highlights: Arrhenius plot of the viscosity for Nd(III) was in good agreement with the Vogel–Fulcher–Tammann equation. The applicability of EQCM methods in ionic liquids was investigated at elevated temperature. The EQCM results at elevated temperature agreed with the theoretical analysis equations. Abstract: In this study, the dependence of the density and viscosity on the concentration of Nd(III) in an ionic liquid, triethylpentylphosphonium bis(trifluoromethylsulfonyl)amide ([P2225 ][TFSA]), was investigated. The density of the ionic liquid showed a linear relationship to the Nd(III) concentration, while its viscosity increased in proportion to the Nd(III) concentration. Furthermore, the Arrhenius plot of the viscosity was in good agreement with the Vogel–Fulcher–Tammann equation: η = η 0 T -1/2 exp [ B / ( T - T 0 ) ] . The applicability of the electrochemical quartz crystal microbalance (EQCM) in ionic liquids at elevated temperatures was proved from the relationship of the resonance frequency and the resistance to the product of the viscosity ( η L ) and the density ( ρ L ) of the ionic liquid samples. The resonance frequency shifts and the resistances were proportional to ( η L ρ L ) 1/2 at 363 K and the results agreed with the theoretical equations used for EQCM analysis.